Metatarsal Head Resections in Diabetic Foot Patients: A Systematic Review - Sanz-Corbalán, Irene (J Clin Med, 2020)
A systematic review and proportional meta-analysis were carried out to investigate the complications that occur after surgical metatarsal head resection in diabetic foot patients. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist recommendations were applied, and the selected studies were evaluated using a Strengthening the Reporting of Observational studies in Epidemiology (STROBE) checklist. PubMed (Medline) and Embase (Elsevier) were searched in December 2019 to find clinical trials, cohort studies, or case series assessing the efficacy of the metatarsal head resection technique in diabetic foot patients. The systematic review covered 21 studies that satisfied the inclusion criteria and included 483 subjects. The outcomes evaluated were the time to heal, recurrence, reulceration, amputation, and other complications. The proportion of recurrence was 7.2% [confidence interval (CI) 4.0–10.4, p < 0.001], that of reulceration was 20.7% (CI 11.6–29.8, p < 0.001), and that of amputation was 7.6% (CI 3.4–11.8, p < 0.001). A heterogeneity test indicated I(2) = 72.6% (p < 0.001) for recurrences, I(2) = 94% (p < 0.001) for reulcerations, and I(2) = 79% (p < 0.001) for amputations. We conclude that metatarsal head resections in diabetic foot patients are correlated with significant complications, especially reulceration.